An enhancement of minimum weighted norm extrapolation of digital audio-audio streaming - Dimaano, Melanie Rose J. and Quiambao, Crispin V. 4 0 16; 5 (2003)
u
Undergraduate Thesis: (B.S. in Computer Studies major in Computer Studies) - Pamantasan ng Lungsod ng Maynila, 2003.
Keywords: 2 -- 0; 6; 20; 20; 2